Time Will Tell: Tense in Narration - Cummins, Sarah (TTR)

(untitled) (Association canadienne de traductologie, 1998)
AbstractTime Will Tell : Tense in Narration — This article examines both linguistic and narrative motivations for the use of present tense in a series of children's novels in French, concluding that the choice is dictated by temporal proximity between the time of the story and the time of the narration, and by the aspectual indeterminacy of the present tense. The choice of tense in the English translation is then discussed. Since the English tense system makes different distinctions and has different effects, various solutions are called for.